2006
DOI: 10.1158/1078-0432.ccr-06-1244
|View full text |Cite
|
Sign up to set email alerts
|

Late Toxicity Is Not Increased in BRCA1/BRCA2 Mutation Carriers Undergoing Breast Radiotherapy in the United Kingdom

Abstract: Purpose:To undertake the first substantial clinical study of breast radiotherapy toxicity in BRCA1 and BRCA2 mutation carriers in the United Kingdom. Experimental Design: Acute and late radiation effects were evaluated in a retrospective study of 55 BRCA1 and BRCA2 mutation carriers treated with radiotherapy for breast cancer at four centers between 1983 and 2002. Individual matching with controls who had sporadic breast cancer was undertaken for age at diagnosis, time since completion of radiation, and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 10 publications
5
36
1
Order By: Relevance
“…Germline BRCA1 mutation carriers indeed exhibit a higher recurrence rate of another primary tumor in the contralateral breast (Verhoog et al, 1998;Haffty et al, 2002) and ovary (Metcalfe et al, 2005); however, this is more likely due to the underlying genetic defect than the DNA damage by previous regimens. A recent report demonstrated that late toxicity is not increased in 37 Brca1 mutation carriers undergoing breast radiotherapy after a medium follow-up of 6.75 years (Shanley et al, 2006). Since the case number is small and radiation-induced cancers often have a long latency (Kirova et al, 2005), a large-scale epidemiological study should be done to clarify this issue.…”
Section: Resultsmentioning
confidence: 99%
“…Germline BRCA1 mutation carriers indeed exhibit a higher recurrence rate of another primary tumor in the contralateral breast (Verhoog et al, 1998;Haffty et al, 2002) and ovary (Metcalfe et al, 2005); however, this is more likely due to the underlying genetic defect than the DNA damage by previous regimens. A recent report demonstrated that late toxicity is not increased in 37 Brca1 mutation carriers undergoing breast radiotherapy after a medium follow-up of 6.75 years (Shanley et al, 2006). Since the case number is small and radiation-induced cancers often have a long latency (Kirova et al, 2005), a large-scale epidemiological study should be done to clarify this issue.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, contradictory results have been achieved about the response to DNA-damaging agents by dermal fibroblasts and lymphocytes derived from BRCA1 mutation carriers, which prevent a definitive assessment on whether the expression of only one allele affects cell behavior (30,31). Moreover, two in vivo studies ruled out an increased toxicity for BRCA1 mutation carriers following either chemotherapy or radiotherapy (32,33). Thus, whether a cellular "BRCA1 heterozygous phenotype" actually exists and whether it is recapitulated by the T47DpS-BR clone selectively under MMC challenge (but not under CDDP challenge or by the MCF7pS-BR2 clone under any stress condition) remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Case participants were women treated for breast cancer with chemotherapy and/or radiotherapy who were known to carry a mutation in the BRCA1 or BRCA2 genes. They were recruited from three genetics centers as part of the study detailed in the associated article, ''Late toxicity is not increased in BRCA1/2 mutation carriers undergoing breast radiotherapy in the United Kingdom (17).'' Of the 55 mutation carriers described in that article, 34 received chemotherapy and are included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to examine the effects of radiation and chemotherapeutic agents in BRCA1 and BRCA2 carriers as one would expect that they could have a greater incidence of normal tissue toxicity from both modalities compared with women with sporadic disease. The accompanying report evaluates the late effects of radiation in a case-control study of BRCA1/2 mutation carriers and sporadic controls in the United Kingdom (17). In conjunction with that study, the toxicity of chemotherapy was also examined to address the following questions: are BRCA1/2 mutation carriers more at risk of acute toxicity from chemotherapy?…”
mentioning
confidence: 99%